2020
DOI: 10.1371/journal.pbio.3000863
|View full text |Cite
|
Sign up to set email alerts
|

Optimising risk-based surveillance for early detection of invasive plant pathogens

Abstract: Emerging infectious diseases (EIDs) of plants continue to devastate ecosystems and livelihoods worldwide. Effective management requires surveillance to detect epidemics at an early stage. However, despite the increasing use of risk-based surveillance programs in plant health, it remains unclear how best to target surveillance resources to achieve this. We combine a spatially explicit model of pathogen entry and spread with a statistical model of detection and use a stochastic optimisation routine to identify w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…Although they suggest some general surveillance principles based on their observations, they do not provide detailed suggestions. Mastin et al [22] examine the spread of plant pathogens. Their paper is close in spirit to our work, in that they focus of optimization of surveillance nodes by building a stochastic optimization model, using Monte Carlo samples.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although they suggest some general surveillance principles based on their observations, they do not provide detailed suggestions. Mastin et al [22] examine the spread of plant pathogens. Their paper is close in spirit to our work, in that they focus of optimization of surveillance nodes by building a stochastic optimization model, using Monte Carlo samples.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, an analysis of the potential spread of the pathogen Xylella fastidiosa in France [ 65 ] identified the primary drivers of infection and incorporated them into a network simulation model, which provided a basis for comparing the performance of several surveillance strategies. Another study of the citrus disease huanglongbing (caused by Candidatus Liberibacter asiaticus) in the United States [ 66 ] evaluated the distribution of surveillance resources as an optimization problem. The researchers found that the sensitivity of available detection methods affected the optimal arrangement of survey sites.…”
Section: Optimization Approaches To Surveillance Designmentioning
confidence: 99%
“…However, rapid responses are not always possible. Pathogens can become established in a host population without the diseases they cause being identified, particularly when effective surveillance systems are not in place [12][13][14][15] or if there is a long incubation period before symptoms [16,17]. Attempts to eliminate or eradicate are also not always successful [18].…”
Section: Introductionmentioning
confidence: 99%